Pengaruh Penggunaan Media Audiovisual Berbasis Film Terhadap Nilai Nasionalisme Peserta Didik di Sekolah Menengah Atas Bina Guna Tanah Jawa - Saragih, Krissi Wahyuni; Suhendar, Aris; Saragih, Sinta Rahayu; Damanik, Desi Auliya; Sipayung, Rohotni (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2025)
This study examines the effectiveness of film-based audiovisual media in enhancing nationalism values among eleventh-grade students at SMA Bina Guna Tanah Jawa in the 2024/2025 academic year. The research was driven by concerns over declining nationalism among younger generations due to globalization and cultural shifts. A quantitative approach with a One Group Pretest-Posttest design was employed, involving 80 purposively selected students. Data were collected through a 20-item Likert scale questionnaire based on four indicators of nationalism from the Ministry of Education and Culture: love for the homeland, pride in national identity, appreciation of cultural diversity, and commitment to unity. Results showed an increase in mean nationalism scores from 71.20 in the pretest to 78.10 in the first posttest, and 82.65 in the second posttest. The greatest improvement was in pride in national identity (+4.1 points), while the lowest was in commitment to unity (+1.7 points). A paired sample t-test yielded a significance value of 0.000 < 0.05, indicating a significant difference before and after treatment. These findings confirm the effectiveness of film-based audiovisual media in fostering nationalism, with further emphasis required on unity and diversity.‎